Alkaline residues and the environment: a review of impacts, management practices and opportunities. (20th January 2016) - Gomes, Helena I.; Mayes, William M.; Rogerson, Mike; Stewart, Douglas I.; Burke, Ian T.
Abstract: Around two billion tonnes of alkaline residues are produced globally each year by industries such as steel production, alumina refining and coal-fired power generation, with a total production estimate of 90 billion tonnes since industrialisation. These wastes are frequently stored in waste piles or landfills, and can be an environmental hazard if allowed to generate dust, or if rainwater infiltrates the waste. This review will focus on the environmental impacts associated with alkaline residues, with emphasis on the leachates produced by rainwater ingress. Many alkaline industrial wastes can produce leachates that are enriched with trace metals that form oxyanions (e.g. As, Cr, Mo, Se, V), which can be very mobile in alkaline water. The management options for the residues and their leachates are also discussed, distinguishing active and passive treatment options. Potential reuses of these materials, in construction materials, as agricultural amendments, and in environmental applications are identified. The mechanisms of carbon sequestration by alkaline residues are assessed, and the potential for enhancing its rate as a climate change off-setting measure for the industry is evaluated. The potential for recovery of metals critical to e-technologies, such as vanadium, cobalt, lithium and rare earths, from alkaline residues is considered. Finally research needs are identified, including the need to better understand the biogeochemistry of highly alkaline systems in order to develop predictable passive remediation and metal recovery technologies. Graphical abstract: Highlights: ∼2 billion tonnes/year of diverse alkaline residues are produced globally. Residue leachates have high pH and are enriched with harmful trace metals. CO2 sequestration and direct reuses are two potential management options. There is significant potential to recover trace metals critical to e-technologies. Better understanding of alkaline biogeochemistry is required to maximise benefits.